Towards a tidal loading model for the Argentine-German Geodetic Observatory (La Plata) - Richter, Andreas Jorg (2017)
We present a regionalized model of ocean tidal loading effects for the Argentine-German Geodetic Observatory in La Plata. It provides the amplitudes and phases of gravity variations and vertical deformation for nine tidal constituents to be applied as corrections to the observatory’s future geodetic observation data. This model combines a global ocean tide model with a model of the tides in the Río de la Plata estuary. A comparison with conventional predictions based only on the global ocean tide model reveals the importance of the incorporation of the regional tide model. Tidal loading at the observatory is dominated by the tides in the Atlantic Ocean. An additional contribution of local tidal loading in channels and groundwater is examined. The magnitude of the tidal loading is also reviewed in the context of the effects of solid earth tides, atmospheric loading and non-tidal loads